Aerobic biodegradation of selected polybrominated diphenyl ethers (PBDEs) in wastewater sewage sludge. (January 2015) - Stiborova, Hana; Vrkoslavova, Jana; Lovecka, Petra; Pulkrabova, Jana; Hradkova, Petra; Hajslova, Jana; Demnerova, Katerina
Highlights: PBDEs were degraded in sewage sludge under aerobic condition by indigenous microflora. Their elimination was reaching 62–78% of their initial amounts. Degradation was significantly enhanced by addition of yeast extract and 4-bromobiphenyl. The half-lives of the most abundant congener BDE 209 ranged between 6.0 and 8.2 months. Abstract: Due to widespread accumulation of polybrominated diphenyl ethers (PBDEs) in our surroundings, it is important to clarify their fate in the environment and the options of their elimination. The aim of this study was to monitor the biodegradation of the most frequent congeners (BDE 28, 47, 49, 66, 85, 99, 100, 153, 154, 183 and 209) under aerobic condition by indigenous microflora in 2 industrially contaminated sewage sludge samples. BDE 209 was detected as the predominating congener in concentrations 685 ng/g and 1403 ng/g dry weight in sewage sludge from WWTPs (waste water treatment plants) Hradec Kralove and Brno, respectively. The total amount of 10 lower PBDEs was 605 and 205 ng/g dry weight, respectively. The aerobic degradation was significantly enhanced by the addition of yeast extract and 4-bromobiphenyl. The total concentrations of all 11 PBDE congeners were lowered and their elimination was detected reaching 62–78% of their initial amounts after 11 months of cultivation. The degradation of most abundant congener BDE 209 followed the first-order kinetics with constant detected between 2.77 × 10 −3 d −1 and 3.79 × 10 −3 d −1 and the half-lives of BDE 209 degradation ranged between 6.0 and 8.2 months. This work clearly demonstrates that both lower brominated PBDEs as well as the major representative BDE 209 could be successfully removed from municipally contaminated sludge under aerobic conditions.